Pengaruh Metode Sterilisasi Permukaan terhadap Kultur Biji Jeruk Japansche Citroen (JC) Citrus limonia Osbeck - TUWO, MUSTIKA; DEWI, ANDI NURHIQMAH; APPA, YOSHELINE GAYATRI DWIMUTIARA; RAMDANI, RESKIA IMTIHANI; SALSABILA, AURELIA (Agrotrop : Journal on Agriculture Science; Vol 12 No 2 (2022)DO - 10.24843/AJoAS.2022.v12.i02.p04, 2022)
Effect of Surface Sterilization Methods on Seed Culture of JC Citrus limonia Osbeck Japansche Citroen (JC) Citrus limonia Osbeck is one type of citrus that is commonly used as rootstock. JC seed propagation through in vitro culture will be more effective. The initiation stage is the first step of in vitro culture to obtain microbial-free explants and initiate the initial growth. At this stage the problem of contamination becomes the main limiting factor. This study aims to obtain the appropriate method of sterilizing of JC orange seed explants in in vitro culture propagation. A total of four sterilization methods have been tested at the Tissue Culture Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Hasanuddin University. The sterilization material used is tween 80, fungicide, 20-30% NaOCl and 90% alcohol. The variables observed in this study were the time of appearance of contamination, the percentage of types of contaminants (bacteria and fungi), the percentage of sterile explants and the percentage of live explants after 28 days of culture. The results showed that the fourth method was the optimal sterilization method with the lowest contamination level of 30% of the other three methods with the highest explant survival rate of 60% compared to the other three methods.